PORTRAYING THE PRACTICE OF READING TO WRITING MOVEMENT: HOW DOES IT WORK FOR STUDENTS’ EFL WRITING? - Rohmah, Galuh Nur (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
This study outlines the practice of the Reading-to-Writing (RtW) movement in EFL writing classes and its contribution to students' writing quality. Process approach writing becomes the underlying principle of the process of discovering meaning in writing. The practice could be strongly seen by exploring essay writing class as it is the stage for students to enter other academic writing. This study was based on teacher-researchers own practice in teaching essay writing. The data were classroom practice and students’ essays. The classroom practice was analyzed based on the theory of process writing, and the essays were analyzed based on the characteristics of a good essay. It was found that the practice of RtW was manifested in the form of annotated bibliography writing. It allows students to be familiar with the anatomy of the article to cite. Furthermore, students were trained to allocate the most relevant information to support their ideas. For further study, exploring another practice of RtW will be worth doing to advance the empirical supports for strengthening the connection of reading and writing.